REVISITING THE CULTURAL IDENTITY OF NYADRAN IN THE GLOBALIZATION ERA: QUALITATIVE ANTHROPOLOGY PERSPECTIVE - Amal, Bakhrul Khair; Supsiloani, Supsiloani; Samosir, Sry Lestari; Moktar, Megan Riri (Al-Qalam, 2024)
In an increasingly integrated and connected era of globalization, cultural identity becomes important in maintaining the diversity and uniqueness of each human group. This research changes the traditional cultural identity of "Nyadran" in the context of the globalization era, using a contemporary anthropological perspective. "Nyadran" is a Javanese cultural tradition that is historically closely linked to local values and local community beliefs. However, along with the development of the era of globalization, this tradition has undergone a significant transformation in an effort to adapt to ever-changing global flows. Using contemporary anthropological research methods, this research involves active participation in the "Nyadran" event as well as interviews with practitioners and participants of this tradition. Data analysis reveals how local elements in "Nyadran" interact with global influences, such as technology, mass media, and changes in social values. In addition, this research explores how globalization can influence the concept of local cultural identity and how local communities react to these changes. The results of this research provide in-depth insight into the dynamics of changing cultural identity in the era of globalization, highlighting the complexity of the relationship between traditional and modern elements in the context of "Nyadran".